Multiculturality and morbidity related by bolivian immigrants in the Family Health Strategy: DOI: 10.15343/0104-7809.201012535 - Rosiane Aparecida de Melo; Lúcia de Lourdes Souza Leite Campinas (O Mundo da Saúde)
Some regions of São Paulo city have a great many Latin American immigrants who work and live in precarious conditions. This research aimed to identify the more frequently reported morbidity by Bolivian immigrants who are users of a USF (Family Health Unit) of São Paulo city. The methodology of this field work is exploratory and descriptive. We did random interviews with a sample of 25 Bolivian immigrants, sewers; they are users of a USF living in the Brás quarter, downtown São Paulo. Results showed the existence of a high rate of tuberculosis cases among them, in addition to dermatological and respiratory problems. Amongst the necessary information in the planning of actions for health directed to particular populations such as of these immigrants, we emphasize morbidity, which may give essential information, being an important health condition indicator for the population and their socio-economic conditions. This study disclosed that immigrants fear being exposed, and avoid making “speculations”. Every assistance action must consider the diversity of people being assisted, respecting their habits, customs and culture. It requires that assistance be adapted to user’s reality so as the implementation of any action in health be guaranteed. The search for social justice must also be part of the life of all health professionals.